Did Abu Hurairah Mudalis?: A Critique of Mahmud Abu Rayya’s View of Thoughts - Gasmelsid, Saadeldin Mansour; Nasution, Alhafidh (Jurnal Usuluddin, 2025)
This article discusses Mahmud Abu Rayya’s thoughts regarding his criticism of Abu Hurairah. He argues that Abu Hurairah is not a Sahabah (Companion of the Prophet) whose Hadiths can be accepted without question because, in his view, Companions could make mistakes in narrating Hadiths. Therefore, the authors analyze these thoughts using a critical approach to obtain valid data for evaluating his perspective. In conclusion, the authors found several enlightening findings that shed light on the accusations made by Abu Rayya against Abu Hurairah. He misunderstood the terminology used in scholarly discussions and confused the concepts of tadlis and mursal sahabi. It is important to distinguish between these two terms because mursal narrations from reliable Sahabah are considered valid and accepted in the field of Hadith scholarship. Therefore, the accusation against Abu Hurairah can not be justified for several reasons. Firstly, Abu Hurairah is a Companion, and all scholars unanimously agree on the trustworthiness of the Prophet’s Companions. Secondly, he misunderstood the term ‘tadlis,’ leading to an incorrect conclusion about Abu Hurairah’s actions.